Introduction to Management in the Hospitality Industry - 531701 Barrows, Clayton W.; Powers, Thomas F., 1931-; Reynolds, Dennis E. (Dennis Edward) (Hoboken, New Jersey : Wiley)
"Readers seeking management careers in hospitality will enter a dynamic industry filled with opportunities. The rewards are many, but so are the challenges. Today's hospitality managers must deal with such complex factors as globalization, terrorism threats, ecotourism, internet commerce, new business and financial models, and rapidly changing consumer demands. Introduction to Management in the Hospitality Industry, 10th Edition gives readers the industry know-how and the management skills needed to thrive in all aspects of the field, from food service to lodging to tourism. The Tenth Edition of Introduction to Management in the Hospitality Industry features both historical perspectives and discussions of new trends in a variety of sectors. This book has the most thorough coverage of the hospitality industry, covering foodservice, lodging, and travel and tourism, hospitality careers, and hospitality management. Upon successful completion of this text, readers will have a strong grasp of the many facets of the hospitality industry"--